PERMAINAN TRADISIONAL MBOJO-BIMA TUTU KALI KU MA..MA.. UNTUK MENSTIMULASI KETRAMPILAN SOSIAL ANAK USIA DINI - Masita Masita; Ihwan Ihwan (Pelangi Jurnal Pemikiran dan Penelitian Islam Anak Usia Dini, 2019)
This article is titled: Traditional Games of Tutu Kali Ku ma..ma .. To Stimulate Early Childhood Social Skill in Mboj-Bima, with the aim being to get the traditional Mbojo-Bima Tutu Kali game ma ma ... ma ... to stimulateskills social early childhood.The form of the traditional game Mbojo-Bima Tutu Kali Ku ma..ma ... is itMy tutu is ma ... ma ...Sa anggonggo wa’i le le..leu .....La Jami mpako ka dui ma mpekeI want to go to the gopa cave ina na’e gepu .....Wio wao salaja waoKido, salaja kodoI asked you to go gopa ina nae gepuThen the palms are arranged then the group leader chooses to take the hands to be pinched or ears while being lifted up to the height of the height so that it will hurt so much by saying the words: Waura do you know ...Then answered: wauraa .......Ngaha kai uta au ??????????Ngaha Kai Uta KarambaThen once the group leader asked by pinching harderNgaha ka uta au ???????????Ngaha kai uta kahoro ma roci hori ..........After that the group leader quickly removes his hand that picks his hand or ear is up to what is chosen by the leader of the game group.After that the game is done, which is hiding in places that are considered not easy for the game keeper to know, saying: Wauraa ...... ?????Waura ........ ?????Waura ....... ?????Waura ....... ?????Then answered: WauraaThen the leader of the game group sees it and says:Akaku waura eda know reThen that’s all that is done until the game is finished and you get who will be punished. The punishment was whether it was pinched, hit by the palm of his hand. Then finished my tutu times ... bro ... Traditional children’s games are born of culture. the game is a heritage, inheritance from our ancestors. So that by preserving it as the culture of our ancestors. But inheritance itself always changes according to the times and the development of culture. The relevance of the traditional game of Mojo-Bima Tutu My time is ma..ma ... to stimulate the skills of early childhood is my tutu game ma ... ma ... has a strong relationship with the growth and development of early childhood especially. With these games, it will help stimulate early childhood. So that the horizons of thinking become very broad, advanced and creative and most importantly the children will feel happy, happy and happy without any burden as a child. Children will be more open to playing with their friends and will increase intimacy between one child and another. Especially if the child has returned to their home, the socialrelations of the community with their friends are not interrupted. Usually children will always remember what they did when at kindergarten school together with their friends, then if their house is close together the children will come to their friend’s house to play again, repeating the game that has been done at the school. So that his social relations are not only with his peers but with his friends ‘brothers, his friends’ siblings, his friends ‘parents, and also his friends’ neighbors. So that social relations have beennurtured and fostered starting from this early age. When they go up to children, adolescents and adults, the lessons and experiences that they have passed through as children will affect their lives later.